2010
DOI: 10.4161/auto.6.1.10323
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib blocks the catabolic process of autophagy via a cathepsin-dependent mechanism, affects endoplasmic reticulum stress, and induces caspase-dependent cell death in antiestrogen–sensitive and resistant ER+ breast cancer cells

Abstract: In recent studies, we and others showed that autophagy is critical to estrogen receptor positive (ER+) breast cancer cell survival and the development of antiestrogen resistance. Consequently, new approaches are warranted for targeting autophagy in breast cancer cells undergoing antiestrogen therapy. Because crosstalk has been demonstrated between the autophagy- and proteasome-mediated pathways of protein degradation, this study investigated how the proteasome inhibitor bortezomib affects autophagy and cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 69 publications
(104 reference statements)
8
51
0
Order By: Relevance
“…2D). We also found a 50% decreased of ERa expression at 24 hours as previously showed by Powers and colleagues and Periyasamy-Thandavan and colleagues (33,34). To evidence the ERa role in p21 regulation, we knocked down ERa with specific siRNA.…”
Section: Resultssupporting
confidence: 85%
“…2D). We also found a 50% decreased of ERa expression at 24 hours as previously showed by Powers and colleagues and Periyasamy-Thandavan and colleagues (33,34). To evidence the ERa role in p21 regulation, we knocked down ERa with specific siRNA.…”
Section: Resultssupporting
confidence: 85%
“…In addition to chloroquine, recent data indicate that bortezomib can also inhibit autophagy via a cathepsin-dependent mechanism that results in p62 up-regulation (12). Our data indicate that p62 up-regulation is critical to its ability to aggregate caspase-8 on the autophagosome (LC3II) in ABT-263-treated cells.…”
Section: Discussionmentioning
confidence: 48%
“…Because p62 is degraded by autophagy, its level can be increased by autophagy inhibition. Specifically, autophagy blockade by chloroquine and/or by cathepsin-dependent inhibition using bortezomib (12) were shown to upregulate p62 expression (Fig. 1C) and to enhance ABT-263-induced caspase cleavage (Fig.…”
Section: Autophagy Inhibition Enhances Abt-263-induced Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Bortezomib is thought to drive cells to programmed cell death by inhibiting the proteasomal degradation of unfolded proteins thereby overwhelming the degradation capacity of the cell and triggering the unfolded protein response. 26,27 This may help explain why bortezomib has an apparent potentiating effect when given as co-therapy with 17-AAG, a heat shock protein 90 inhibitor in patients with relapsed or refractory MM. 12 As regards to another component of the proteasome complex, namely PSMA5 it has been reported that low plasma levels are associated with longer PFS in mantle cell lymphoma treated with bortezomib.…”
Section: Discussionmentioning
confidence: 99%